Multi-layer ultrasonic imaging of as-built wire + arc additive manufactured components - Zimermann, Rastislav; Mohseni, Ehsan; Lines, David; Vithanage, Randika K. W.; MacLeod, Charles N.; Pierce, Stephen Gareth; Gachagan, Anthony; Javadi, Yashar; Williams, Stewart W.; Ding, Jialuo (Elsevier, 2021)
Non-Destructive Evaluation (NDE) of metal Additively Manufactured (AM) components is crucial for the identification of any potential defects. Ultrasonic testing is recognised for its volumetric imaging capability in metallic components and high defect sensitivity. However, conventional ultrasonic techniques suffer from challenges when deployed on components with curved and non-planar geometries, such as those often encountered in AM builds. The body of work introduces the concept of inspection of Wire+Arc Additive Manufacture (WAAM) components from their non-planar as-built surface, eliminating the requirement for post-manufacturing machining. In-situ or post-manufacturing inspection is enabled via an autonomously deployed conformable phased array roller-probe deploying Synthetic Aperture Focusing Technique (SAFT)-surface finding and multi-layer adaptive Total Focusing Method (TFM) algorithms, for fully focussed imaging of the as-built WAAM component. The concept of the imaging approach is demonstrated by inspection, through the as-built surface, of two titanium WAAM components, one containing reference bottom-drilled holes, and the other with intentionally introduced Lack of Fusion (LoF) defects. The TFM images of the WAAM components feature sufficient Signal-to-Noise Ratio to enable defect detection along with strong agreement against reference X-Ray CT data, confirming the competency of the approach for volumetric or layer-specific inspection of as-built WAAM components.
Keywords: Ultrasound inspection of additive manufacturing; ultrasound array imaging; Adaptive Total Focusing Method (ATFM); Full Matrix Capture (FMC); Synthetic Aperture Focusing Technique (SAFT); Wire + Arc Additive Manufacture (WAAM)